(untitled) (RevistAleph, 2019)
The prolongation of that period of life referred to as youth is well documented and accepted in the literature relating to youth. Dwyer and Wynn (2001) wrote of the new meaning of adulthood and the problem facing youth as they make a transition to a target zone that is constantly changing. The certainty of making a smooth transition to adulthood is no longer, if it ever were, assured. This study looks at a number of youth in what is often referred to as the transition phase to adulthood. They are in five different countries Brazil, France, Switzerland, Australia, and United States of America on four different continents. The individuals interviewed were generally between 18 – 30 years of age. They were asked a variety of questions relating to their prospects, hopes and aspirations for the future.